Development of an Effective Medical Transdermal Patch from Piper sarmentosum Roxb. extract for Inhib iting Staphylococcus aureus - Masaeng, Aleena; Suwannakae, Bharadee; Kraipasspong, Sidaphat; Dumkua, Tanyaratana; Boontem, Ratchada; Piyaboon, Orawan (Journal of Health Science of Thailand, 2018)
Wound infection caused by Staphylococcus aureus is considered a major bacterial infection. Piper sarmentosum Roxb. extract has been proposed to treat wound infections as an alternative to antibiotics to avoid side effects and antibiotic resistance. This research aimed to study the efficiency of crude extract from P. sarmentosum Roxb. against S. aureus and to develop a medical transdermal patch that could cure chronic wound infection. In this study, leaves of P. sarmentosum Roxb were extracted with 95% methanol solvent. The crude extract was investigated for antibacterial activity against S. aureus by agar disc diffusion method. After detection of inhibition of the bacterial growth, 22% (w/v) crude extract was applied to a medical transdermal patch. The medical transdermal patch was found to be as significantly efficacious as the patch of 2% (w/v) streptomycin in inhibiting the growth of S. aureus. In addition, there was no significant difference between Piper sarmentosum Roxb. patch and commercial medical transdermal patches in the inhibition of the bacterial growth. In conclusion, medical transdermal patch of P. sarmentosum Roxb. extract could be used as a disinfectant product.